Enhancing Islamic Education Quality through Educational Supervision and ICT - Posangi, Said Subhan; Lundeto, Adri; Labaso, Syahrial; Anwar, Herson; Damopolii, Mujahid (Jurnal Ilmiah Peuradeun, 2025)
This study explored the role of education supervisors in enhancing the professional competence of Islamic Religious Education (PAI) teachers in madrasahs across six provinces in Sulawesi, Indonesia. The research responds to concerns over the uneven quality of PAI instruction, which is often hindered by weak supervision, limited training, and inadequate use of digital tools. Employing a qualitative approach, the data were collected through semi-structured interviews, participatory observations, and document analysis. Thematic analysis was used to identify key supervisory functions and challenges. The findings revealed that education supervisors significantly contributed to improving teacher quality through classroom observations, performance evaluations, personalized mentoring, and facilitation of professional training—particularly in the integration of ICT. However, supervision was often constrained by internal factors such as teacher motivation and seniority, as well as external barriers like limited infrastructure and resistance to innovation. To address these challenges, the study presented an ICT-based supervisory model that emphasizes collaboration, reflective practice, and strategic support. This research contributes to the literature by offering a contextualized framework for supervision in Islamic education and proposing scalable strategies for professional development. It also provides global relevance for Islamic educational institutions facing similar structural and pedagogical constraints.